Quadrupole moments of exotic carbon isotopes (9C, 11C, 17C and 19C) including core polarization effect - A. Saeed, Wael A. Saeed (Iraqi Journal of Physics, 2019)
Quadrupole Q moments and effective charges are calculated for 9C, 11C, 17C and 19C exotic nuclei using shell model calculations. Excitations out of major shell space are taken into account through a microscopic theory which are called core-polarization effects. The simple harmonic oscillator potential is used to generate the single particle matrix elements of 9,11,17,19C. The present calculations with core-polarization effects reproduced the experimental and theoretical data very well.